Frontiers in conservation science - Frontiers Research Foundation (Frontiers Media S.A, 2020)
"Frontiers in Conservation Science is a multidisciplinary open access platform dedicated to the publication of ideas, reports, methods and techniques that can be applied to biodiversity conservation and management. The aim of the journal is to encourage collaboration between scientists, stakeholders and civil society to advance the conservation and management of the world's biodiversity."--Publisher
Keywords: Biodiversity conservation : Periodicals; Biodiversity conservation